2011
DOI: 10.1111/j.1440-1681.2011.05536.x
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin abolishes core temperature, but not cardiovascular or renal, responses to lipopolysaccharide in conscious lambs

Abstract: 1. Core temperature (Tc), cardiovascular and renal responses to lipopolysaccharide (LPS), as well as the role of endogenously produced prostaglandins (PG) in influencing these responses, were investigated in the present study in conscious, chronically instrumented lambs. 2. Core temperature, mean arterial pressure, heart rate (HR), renal blood flow (RBF) and several parameters of renal function were measured for 30 min before and for 5 h after intravenous injection of 0.03 μg/kg of the LPS Salmonella abortus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this study, no effects of chronic indomethacin treatment were observed in either stressed or non-stressed animals. Little is known about the effects of indomethacin on anxiety, but Smith et al [99] reported that indomethacin had no significant effect on the cardiovascular response of conscious lambs to lipopolysaccharide. Therefore, it is not surprising that our study observed the inefficacy of indomethacin in reducing symptoms of anxiety in stressed mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no effects of chronic indomethacin treatment were observed in either stressed or non-stressed animals. Little is known about the effects of indomethacin on anxiety, but Smith et al [99] reported that indomethacin had no significant effect on the cardiovascular response of conscious lambs to lipopolysaccharide. Therefore, it is not surprising that our study observed the inefficacy of indomethacin in reducing symptoms of anxiety in stressed mice.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we showed that there is an interaction between ANG II and NO in influencing cardiovascular homeostasis as well as the arterial baroreflex of heart rate early in life, which appears to be developmentally regulated [46]. We have also previously reported on the haemodynamic responses to INDO alone [12,13,39], as well as L-NAME alone [30][31][32]46] in conscious lambs at different stages of post-natal maturation. To these findings, the present observations support a further modulatory role for PGs in influencing the vasoconstrictor effects of ANG II soon after birth.…”
Section: Discussionmentioning
confidence: 85%